Host immune response to infectious bronchitis virus Q1 in two commercial broiler chicken lines. (May 2021) - Manswr, Basim; Ball, Christopher; Forrester, Anne; Chantrey, Julian; Ganapathy, Kannan
Abstract: This study investigated the pathogenesis of infectious bronchitis virus ( Gammacoronavirus ) strain Q1 in two commercial broiler chicken lines, and the host immune response to infection. Chicks from each line were grouped into either infected or control. Following Q1 infection at day-old, fast (Line-A) and slow (Line-B) growing chicks were monitored for clinical signs and body weights. At 3, 7, 9, 14, 21 and 28 days post infection (dpi), five birds were humanely euthanised, and trachea, kidney and proventriculus tissues were collected for quantitative RT-PCR and histopathology. Blood was collected weekly to determine IBV-specific ELISA antibody titres. Q1 infection significantly reduced the body weights of Line-A chicks at 14 and 21 dpi, but there were no significant differences in Line-B. Through qRT-PCR, significantly higher viral loads were found in the trachea, proventriculus and kidney tissues of Line-A chicks at 7–9 dpi. At day-old and at 28 dpi, the mean antibody titre in Line-B was notably higher than Line-A. Significant IFN-α mRNA expression was noted in the trachea and kidneys of Line-A, whereas no change occurred in Line-B. Chicks in Line-B, compared to those in Line-A, demonstrated a tissue-dependent increase of IFN-β, TLR3, IL-1β and IL-6 and LITAF gene transcription responses to IBV Q1. It appears that the level of maternal antibodies, growth rates, and other inherent host genetic factors could have influenced the differences in viral loads and immune responses. Highlights: Reduction in the body weights of Line-A broiler chicks infected with IBV Q1 Lower IBV Q1 viral load in tissues of Line-B chicks Earlier IBV Q1 viral clearance in Line-B chicks Higher mRNA expression of tracheal IFN-α and TLR3 in IBV Q1 infected Line-A chicks Anti-IBV maternal antibodies modulate IBV Q1 infection and immune responses